Peran Bumdes Dalam Membangun Kewirausahaan Dan Kemandirian Desa (Studi Kasus Bumdes Mugirahayu, Desa Lebak Herang, Kecamatan Ciwaru, Kabupaten Kuningan, Jawa Barat) - Hadiyat, Yayan (Jurnal Manajemen, 2018)
Village Owned Enterprises (BUMDES) have a strategic role in improving the economy and village independence. Since the issuance of Law No. 32/2004 concerning Regional Government, the number of BUMDES until 2017 has reached 18,446. The main challenge for the existence of BUMDES is to be able to become a driver of economic development in the village. In many regions, BUMBDES has contributed to accelerate rural development and encourage the economic independence in the village. However, many BUMDES are stagnant, so that needs field studies to see the problems and the way of efforts to overcome them, and the result can bu used as models for the development of BUMDES in other regions, and can be used as national models. This article presents the results of case study of the MUGIRAHAYU BUMDES in Lebakherang Village, Subdistrict of Ciwaru, Kuningan District, West Java, where since the beginning of its establishment it has experienced success and gave benefits for improving the community's economy in the village, but many the BUMDES has experienced ups and downs, even stagnating. Some of the problems obtained from the field, namely the existence of organizational and the sussession problems, and emerged the existence of organizational dependence from several administrators, so that a good community spirit (paguyuban) in the village is unable to encourage BUMDES MUGIRAHAYU to build reliablility of the organization of BUMDES and entrepreneurial for the community. The New Public Management (NPM) and Fadel Model (2008), can be proposed to overcome the problems that occur in BUMDES and be able to strengthen sustainability of organizational life and building entrepreneurship. By strengthening transparency, accountability and professionalsm of management teams, BUMDES would be able to push the business of the community in the villages and build community entrepreneurship through exploring the local potential and endowment, so that it can build the economic independence in the village.